An Evaluation on Iran International Public Health Summer School in Relation to its Efficacy Based on Participants' Experience and Opinions - Aidin Parnia; Nikoo Yamani; Ahmadreza Zamani; Shervin Badihian; Navid Manouchehri; Maryam Fakhri (Advanced Biomedical Research, 2017)
Background: A serious challenge to educate health staff for public health is to appear encouraging enough to persuade them for learning issues on this field and implementing new educational methods and innovative ways. Iran International Public Health Summer School (IPHS) made an effort to provide medical sciences students with a fortune to get familiar with and involved in public health. This study intended to evaluate the efficacy of this event. Materials and Methods: This cross-sectional study was performed in March–April 2015 by the help of an electronic self-administered questionnaire filled out by 49 Iranian participants 6 months after IPHS2014. The questionnaire assessed the main goals in seven main domains: Interest, activities, and general knowledge in the field of public health, general skills, educational methods, educational and executive schedules, and general satisfaction. Results: Average scores of all domains were >3 (the mean), and all were statistically significant. The highest average score belonged to educational methods (3.92) and the lowest was calculated for the item regarding participants' activities on public health (3.5). No significant difference was found between positive answers of individuals who were interested or active in public health prior to the event and those who had no background. Conclusions: We believe IPHS was a unique instance in Public Health Education in Iran. Considering the level of success of this program to reach its goals for both students' with or without any previous background on public health, it is recommended as a general model to be simulated in other developing countries.